Sincronização do ciclo estral em vacas nelore com prostaglandi na F2-alfa análoga (ICI-80.996, Cloprostenol) por via intramuscular - Basile, João Roberto; Benedito, Vanderlei A. (Semina: Ciências Agrárias, 1980)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} @font-face {font-family:"Microsoft Sans Serif"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627421663 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0pt; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 85.05pt 70.85pt 85.05pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> The objective of this study is to determine the efficiency of PGF2-OL analogue (Cloprostenol, ICI-80.996) in the synchronization of the estrous cycle and the fertility level in Nelore cows from a farm adjacent to Londrina, Paraná State. On the first day of the trial, 132 cows were selected after genital examination, the majority of them, 7 to 9 months after parturition and the rest barren during the previous year. These animals were distributed at random into three groups of 44 each. Groups I and II received two doses of 0.5 mg of Cloprostenol through intramuscular route 11 days apart. Group I animals were inseminated twice at 72 and 96 hours after while those in group II were inseminated once, aproximately 12 hours after the heat detection by teaser bulls with chin-ball. The third group received no treatment and served as control, following the same scheme as group II over a fixed period of 21 days. The results obtained were as follows: Group I - without having any concern over the symptoms of heat, 24 (54,54%) cows became pregnant and from the other 20,70% repeated a normal cycle. Group II-between the 2nd and the 8th day, 42 (95,45%) cows showed signs of heat and were inseminated, 15 of them (34,09%) became pregnant and from the 27 animals that were not pregnant 18 (66.66%) returned to heat 19 to 22 days later, confirming the data observed in the previous group. Group III - heat and insemination rates of43 (97.72%) cows resulted in 16 (36.36%) pregnancies while rest of the animals returned to the regime of natural service. The conception rate between groups were not significantly different (P > 0.05).